Cardiac telerehabilitation: A novel cost-efficient care delivery strategy that can induce long-term health benefits. (November 2017) - Frederix, Ines; Solmi, Francesca; Piepoli, Massimo F; Dendale, Paul
Background: Finding innovative and cost-efficient care strategies that induce long-term health benefits in cardiac patients constitutes a big challenge today. The aim of this Telerehab III follow-up study was to assess whether a 6-month additional cardiac telerehabilitation programme could induce long-term health benefits and remain cost-efficient after the tele-intervention ended. Methods and results: A total of 126 cardiac patients first completed the multicentre, randomised controlled telerehabilitation trial (Telerehab III, time points t0 to t1 ). They consequently entered the follow-up study (t1 ) with evaluations 2 years later (t2 ). A quantitative analysis of peak aerobic capacity (VO2 peak, primary endpoint), international physical activity questionnaire self-reported physical activity and HeartQoL quality of life (secondary endpoints) was performed. The incremental cost-effectiveness ratio was calculated. Even though a decline in VO2 peak (24 ± 8 ml/[min*kg] at t1 and 22 ± 6 ml/[min*kg] at t2 ; P ≤ 0.001) was observed within the tele-intervention group patients; overall they did better than the no tele-intervention group ( P = 0.032). Dividing the incremental cost (−€878/patient) by the differential incremental quality-adjusted life years (QALYs) (0.22 QALYs) yielded an incremental cost-effectiveness ratio of –€3993/QALY. Conclusions: A combined telerehabilitation and centre-based programme, followed by transitional telerehabilitation induced persistent health benefits and remained cost-efficient up to 2 years after the end of the intervention. A partial decline of the benefits originally achieved did occur once the tele-intervention ended. Healthcare professionals should reflect on how innovative cost-efficient care models could be implemented in standard care. Future research should focus on key behaviour change techniques in technology-based interventions that enable full persistence of long-term behaviour change and health benefits. This study is registered in the ISRCTN registry (ISRCTN29243064).